Green protectionism in the European Union: How Europe's biofuels policy and the renewable energy directive violate WTO commitments - Fredrik Erixon; Roderick Abbott (European Centre for International Political Economy (ECIPE), 2009)
This paper examines the trade-policy consequences of current approaches in the European Union towards biofuels. The EU uses a broad range of measures to subsidise the production of biofuels in Europe and to protect them from foreign competition. It is one of the biggest manifestations of "green protectionism" (...)
Keywords: 330; Biokraftstoff; EU-Energiepolitik; WTO-Recht